All-cause and cause-specific mortality in rheumatoid arthritis, psoriatic arthritis and axial spondyloarthritis: a nationwide registry study. (4th April 2022) - Kerola, Anne M; Kazemi, Amirhossein; Rollefstad, Silvia; Lillegraven, Siri; Sexton, Joseph; Wibetoe, Grunde; Haavardsholm, Espen A; Kvien, Tore K; Semb, Anne Grete
Abstract: Objectives: To explore mortality and causes of death among Norwegian patients with RA, PsA and axial spondyloarthritis (axSpA) compared with the general population by conducting a nationwide registry-based cohort study. Methods: Patients with RA, PsA and axSpA were identified from the Norwegian Patient Registry based on ICD-10 codes between 2008 and 2017. Using age as the time variable, all-cause and cause-specific mortality were estimated between 2010 and 2017 with the Kaplan–Meier estimator and the cumulative incidence competing risk method, respectively. Sex-, education level-, health region- and age group-adjusted hazard ratios (HRs) for mortality were estimated using Cox regression models. Results: We identified 36 095 RA, 18 700 PsA and 16 524 axSpA patients (70%, 53% and 45% women, respectively). RA and axSpA were associated with increased all-cause mortality (HR 1.45 [95% CI: 1.41, 1.48] and HR 1.38 [95% CI: 1.28, 1.38], respectively). Women but not men with PsA had a slightly increased mortality rate (HR 1.10 [95% CI: 1.00, 1.21] among women and 1.02 [95% CI: 0.93, 1.11] among men). For all patient groups as well as for the general population, the three leading causes of death were cardiovascular diseases, neoplasms and respiratory diseases. RA patients had increased mortality from all of these causes, while axSpA patients had increased mortality from cardiovascular and respiratory diseases. Conclusion: Even in the era of modern treatments for IJDs, patients with RA and axSpA still have shortened life expectancy. Our findings warrant further attention to the prevention and management of comorbidities.